Making sense of data a self-instruction manual on the interpretation of epidemiological data - Abramson, J. H. (Joseph Herbert), 1924-; Abramson, Z. H. (New York ; Oxford : Oxford University Press, 2001)
This is a self-instructed manual on the interpretation and use of epidemiologic data that deal with the basic concepts and skills needed for appraising published reports or study findings.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- Statistical methods; Epidemiology -- Statistical methods -- Problems, exercises, etc